(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the impact of artificial intelligence technologies on contemporary political processes. The opportunities, such as the use of AI in election campaigns, individual outreach to voters, and monitoring public sentiment are examined. The dangers of deepfake technologies are explored through the examples of South Korea, the United States and the case of Grok AI. Additionally, the role of AI in the legal sphere, the European Union’s AI Act, and ethical-legal issues are discussed. The article’s findings demonstrate that artificial intelligence, along with innovation in political processes, may also pose a threat to democratic institutions.